Economizer Manufacturing Process Optimization in Boiler Efficiency Improvement: A Literature Review - Faizal, Faizal; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
Boilers are one of the important components in the industrial sector, with their thermal efficiency largely dependent on the ability to utilize the heat energy produced. Economizer is the main device used to improve boiler efficiency by utilizing residual heat from flue gases to heat feed water, thereby reducing fuel consumption and greenhouse gas emissions. This research aims to review the literature related to optimizing the economizer manufacturing process, including material selection, design, and production technology, in order to improve boiler thermal efficiency. The review shows that materials such as stainless steel and copper have a great contribution in improving thermal conductivity and corrosion resistance. In addition, new material innovations, such as ceramic and polymer composites, offer significant potential for improving economizer performance. On the other hand, manufacturing processes such as high-precision welding and strict quality control prove instrumental in ensuring the structural integrity of the economizer. By optimizing manufacturing processes, boiler efficiency can increase by up to 15%, while supporting sustainability by reducing greenhouse gas emissions. This research confirms that further development in economizer design, materials and manufacturing technologies is necessary to meet the needs of a sustainable industry. Thus, economizer is not only a solution for energy efficiency but also a strategic step in supporting a more environmentally friendly energy system.